The distributed parallel genetic algorithm on the ad hoc network - Afifi, Nima; Tavakoli, Hassan (Journal of Advanced Computer Science & Technology, 2015)
Today, mobile computing is one of the important issues in computer and network sciences. Using the processing power of mobile devices purposefully for solving complex issues is one of the research fields for researchers. One of the important issues in the optimization which needs a high processing power for finding the best possible answer is travelling salesman problem. In this paper, by providing a method based on the distributed parallel genetic algorithm on a number of mobile nodes in the Ad Hoc network, it was attempted to increase the speed of finding the best answer for the travelling salesman algorithm.